Effect of Thermal Radiation on Biomagnetic Fluid Flow and Heat Transfer over an Unsteady Stretching Sheet - Alam, Md. Jahangir; Murtaza, Md. Ghulam; Tzirtzilakis, Efstratios E.; Ferdows, Mohammad (Computer Assisted Methods in Engineering and Science, 2021)
This study examines the influence of thermal radiation on biomagnetic fluid, namely blood that passes through a two-dimensional stretching sheet in the presence of magnetic dipole. This analysis is conducted to observe the behavior of blood flow for an unsteady case, which will help in developing new solutions to treat diseases and disorders related to human body. Our model is namely biomagnetic fluid dynamics (BFD), which is consistent with two principles: ferrohydrodynamic (FHD) and magnetohydrodynamic (MHD), where blood is treated as electrically conductive. It is assumed that the implemented magnetic field is sufficiently strong to saturate the ferrofluid, and the variation of magnetization with temperature may be approximated with the aid of a function of temperature distinction. The governing partial differential equations (PDEs) converted into ordinary differential equations (ODEs) using similarity transformation and numerical results are thus obtained by using the bvp4c function technique in MATLAB software with considering applicable boundary conditions. With the help of graphs, we discuss the impact of various parameters, namely radiation parameter, unsteady parameter, permeability parameter, suction parameter, magnetic field parameter, ferromagnetic parameter, Prandtl number, velocity and thermal slip parameter on fluid (blood) flow and heat transfer in the boundary layer. The rate of heat transfer and skin friction coefficient is also computationally obtained for the requirement of this study. The fluid velocity decreases with increasing values of the magnetic parameter, ferromagnetic interaction parameter, radiation parameter whereas temperature profile increases for the unsteady parameter, Prandtl number, and permeability parameter. From the analysis, it is also observed that the skin friction coefficient decreases and the rate of heat transfer increases respectively with increasing values of the ferromagnetic interaction parameter. The most important part of the present analysis is that we neither neglect the magnetization nor electrical conductivity of the blood throughout this study. To make the results more feasible, they are compared with the data previously published in the literature and found to be in good accuracy.